Configuring the patient as clinical research subject in the UK national health service - Adams, Mary (Anthropol Med, 2015)
This paper examines a central image in UK academic clinical research – the patient as altruistic research subject – by means of an interpretive review of social science, bioethical and bioscience research and development policy literatures. The review examines this image as it is indicted in discussions about the nature of clinical science; is consolidated in the ethical regulation of this science; and is articulated in recent bioscience research and development government initiatives. Drawing on Strathern's notion of the virtual (public-sector) subject, the review identifies the anticipation of NHS patients as alternatively ‘available’ or ‘entitled’ to the expanding translational medicine industry.